Metabolites: a converging node of host and microbe to explain meta-organism - Chakraborty, Nabarun (Frontiers in Microbiology, 2024)
Meta-organism that encompasses the host and resident-microbiota plays significant role in combatting the diseases and responding to stress. Hence, there is a growing traction to build a knowledgebase about this ecosystem, particularly to characterize the bidirectional relationship between host and microbiota. In this context, metabolomics emerges as the major converging node of this entire ecosystem. Systematic comprehension of this resourceful omics component can elucidate the organism-specific response trajectory and the communication grid across the ecosystem embodying meta-organism. Translating this knowledge into designing postbiotic nutraceuticals and next generation therapy is ongoing. Its major hinderance is a significant knowledge gap about the underlying mechanisms that maintain delicate balance within this ecosystem. To bridge this knowledge gap, we presented a holistic picture of the available information with a primary focus on the microbiota-metabolite relationship dynamics. A major topic of this article is the gut-brain axis and the participating microbial metabolites that impact the cerebral functions and its fitness.